Pengurusan buangan sisa pepejal: penggunaan instrumen berasaskan pasaran sebagai satu alternatif penyelesaian - Rospidah Ghazali,; Chamchuri Siwar, (Environmental Management Society, Malaysia, 2001)
The issue of solid waste disposal is becoming more critical in environmental management in Malaysia. Solid waste disposal is one of the most important environmental problems faced by the local authorities in this country. Major urban areas are estimated to generate waste at the rate of 1kg/capita/day, a figure which is much higher compared to European urban areas. As a consequent of economic development, population density, urbanization and industrialization processes the solution to solid waste problem is no longer a simple one. To achieve the best solution involves policy planning, the formulation of strategies and multidimensional actions which includes economy, socio-cultural, technical, health and political will. In Malaysia, command and control mechanism is used in controlling behavior and activities related to solid waste disposal. However, there are numerous weaknesses in this mechanism. Therefore, in order to achieve a more efficient solid waste management a number of alternative options especially through the use of economic tools are suggested for the reduction and prevention of disposal of solid waste as has been successfully practiced in some countries